Game Edukasi Infinity Investigation dengan menggunakan Unity Enggine berbasis Android Di Kejaksaan Negeri Dumai - Arvan Ariadi; Mustazihim Suhaidi; Ari Sellyana (JUTEKINF (Jurnal Teknologi Komputer dan Informasi), 2024)
The development of science and technology encourages the learning process to be more applicable and interesting in an effort to improve the quality of education. One of the media that can be used for learning is a game or game application. Educational genre games can be used by the Dumai State Prosecutor's Office, which is based in the City of Dumai, as one of the media in holding digital forensic themed outreach, especially for high school students in Dumai City. The ineffectiveness of the socialization was evident from the low interest and enthusiasm of the public for the socialization held by the Dumai State Prosecutor's Office, especially among high school students in Dumai City. The ineffective socialization on the theme of digital forensics held by the Dumai State Prosecutor's Office in the form of the presentation of material using PowerPoint media caused high school students to be bored while participating in socialization activities. Therefore, educational games with the theme of digital forensics can help the Dumai State Prosecutor's Office carry out interesting and interactive outreach to educate high school students regarding digital forensic materials in the City of Dumai. With game media, material packaged in the form of a game will make students excited about participating in socialization seminars. In this study, the game was designed to be built using the Unity Engine application and designed using storyboards, storylines, and Unified Modeling Language (UML) flowcharts. From the implementation results, it can be concluded that educational games can help the Dumai District Attorney overcome the ineffectiveness of socialization on the theme of digital forensics.